2024
DOI: 10.1055/s-0043-1760767
|View full text |Cite
|
Sign up to set email alerts
|

Vascularized Reconstruction of Recalcitrant Clavicular Nonunion with the Medial Femoral Condyle Free Flap: A Systematic Review of the Literature

Abstract: Recalcitrant clavicular nonunion is an uncommon but challenging problem. Vascularized bone reconstruction is not first-line therapy due to complexity and donor morbidity, though it has utility in select cases. A systematic review of Embase and Medline databases was undertaken for cases of medial femoral condyle reconstruction for clavicle nonunion. Ten studies met inclusion, encompassing 26 patients. Mean age was 38.9 years. Ten patients were male and 16 female. Mean time of nonunion was 37.79 months prior to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
(102 reference statements)
0
0
0
Order By: Relevance
“…36 Evidence is mounting that the MFC is well poised for use in recalcitrant nonunions and hostile wound beds. [37][38][39] Recently, a multi-institutional retrospective case series by Guzzini et al reported a 94.9% union rate for MFC reconstructions of long bone recalcitrant nonunions. 40 These findings are corroborated by the high union rates reported in this study.…”
Section: Discussionmentioning
confidence: 99%
“…36 Evidence is mounting that the MFC is well poised for use in recalcitrant nonunions and hostile wound beds. [37][38][39] Recently, a multi-institutional retrospective case series by Guzzini et al reported a 94.9% union rate for MFC reconstructions of long bone recalcitrant nonunions. 40 These findings are corroborated by the high union rates reported in this study.…”
Section: Discussionmentioning
confidence: 99%